2000
DOI: 10.4049/jimmunol.164.4.1807
|View full text |Cite
|
Sign up to set email alerts
|

The Balance of Protein Kinase C and Calcium Signaling Directs T Cell Subset Development

Abstract: Development of naive T cells into type 1 (Th1, Tc1) or type 2 (Th2, Tc2) effector cells is thought to be under the control of cytokines. In this study, we show that when both IL-12 and IL-4 are present, murine and human T cell differentiation is regulated by the balance of protein kinase C (PKC) and calcium signaling within T cells. Although both biochemical signals were required for T cell activation via the TCR, altering the balance between them redirected type 1 cells to type 2 and vice versa. Stimulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 45 publications
4
76
0
1
Order By: Relevance
“…Indeed, the disruption of LAT/ PLC-g signalosome assembly reduces Erk and Ca 2+ activation (29,30) and despite normal Foxp3 expression, LAT-or PLCg-deficient Tregs are ineffective in controlling the proliferation of effector T cells (29)(30)(31). In addition, sustained Erk activity and calcium signaling impact on the Th1/Th2 polarization, promoting Th1 differentiation (43)(44)(45). Finally, it has been shown that TCRdependent signals promote epigenetic modifications (46) that are crucial for the acquisition of a functional and stable Treg phenotype by developing Foxp3 + cells (47).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the disruption of LAT/ PLC-g signalosome assembly reduces Erk and Ca 2+ activation (29,30) and despite normal Foxp3 expression, LAT-or PLCg-deficient Tregs are ineffective in controlling the proliferation of effector T cells (29)(30)(31). In addition, sustained Erk activity and calcium signaling impact on the Th1/Th2 polarization, promoting Th1 differentiation (43)(44)(45). Finally, it has been shown that TCRdependent signals promote epigenetic modifications (46) that are crucial for the acquisition of a functional and stable Treg phenotype by developing Foxp3 + cells (47).…”
Section: Discussionmentioning
confidence: 99%
“…nAChR subtypes, causing the opening of receptor ion channels, leading to subtle changes in intracellular levels of calcium ions (32,33). Normal maturation of thymocytes involves TCR ligation, which itself induces calcium ion influx (34,35). In this fashion exogenous nicotine may mimic TCR signals via ionotropic means and effectively change the way T cells normally mature.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the strength of the signals mediated through TCRs can influence Th cell lineage commitment (5,(13)(14)(15)(16). It is possible that activation of T cells via TCRs may polarize the cells toward being Th1 or Th2 cells, and these cells further differentiate and proliferate in response to IL-12 or IL-4, respectively (17).…”
Section: D4mentioning
confidence: 99%